Folic Acid Attenuates MSG-Induced Teratogenicity during A 2-Month Pregnancy by Preventing Neural Crest Cell Destruction and Malformation in Chick Embryo Models - Pintarasri , Suriyan; Plakornkul , Vasana; Viravud , Yadaridee; Payuhakrit , Witchuda; Rungruang, Thanaporn (Trends in Sciences, 2023)
Monosodium glutamate (MSG), commonly used as a food enhancer, has been reported to have teratogenicity during the first 3 days of development. Furthermore, the neural crest cells (NCCs) are crucial for embryonic development during organogenesis. The present study aimed to investigate the treatment effect of folic acid (FA) on MSG-induced teratogenicity, focusing on the toxicity and teratogenic effects on somatic and neural crest cells in chick embryos as models. Six hundred and fifty fertilized eggs were divided into control, FA, MSG, and MSG with FA groups. The chemicals were administered, and the results were investigated after 3 days of incubation. The morphology and histology were studied using stereomicroscopy and hematoxylin and eosin staining, respectively. The NCC population was confirmed by the presence of HNK-1 using immunohistochemistry. The finding showed that the MSG at 2 mg/kg of egg weight induced retardation, tissue malformation, craniofacial, and heart defects, whereas the FA alleviated those adverse effects and reduced the MSG-induced NCCs destruction in the eyes, heart, stomach, and nerves. In conclusion, although MSG harms embryos, FA effectively diminished its teratogenicity in the chick embryo model. These experimental protocols are beneficial for teratogenic studies on preventing birth defects that are harmful to the embryo. HIGHLIGHTS The 4 mg/kg egg weight of monosodium glutamate exposure leads to chick embryo lethality Folic acid treatment is effective at 2 mg/kg of monosodium glutamate exposure Folic acid is essential for supervised neural crest cell functions following monosodium glutamate-induced teratogenesis These experimental protocols are beneficial for teratogenic studies GRAPHICAL ABSTRACT